2021
DOI: 10.1093/ofid/ofab141
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem-Vaborbactam as Salvage Therapy for Ceftazidime-Avibactam-, Cefiderocol-Resistant ST-512 Klebsiella pneumoniae–Producing KPC-31, a D179Y Variant of KPC-3

Abstract: A 68-year-old man had recurrent bacteremia by Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae resistant to ceftazidime-avibactam and cefiderocol. The sequencing of a target region showed that it harbored a KPC-3 variant enzyme (D179Y; KPC-31), which confers resistance to ceftazidime-avibactam and restores meropenem susceptibility. The patient was successfully treated with meropenem-vaborbactam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The strains also produced the following ESBLs: CTX-M-15, OXA-1, OXA-9, TEM-1. Among the 247 KPC-Kp strains we performed sequence typing on 41 isolates; all KPC-Kp tested belonged to the ST512 and carried the bla KPC-3 gene [22]; bla genes encoding OXA-9 and SHV-11 were also detected.…”
Section: Study Populationmentioning
confidence: 99%
“…The strains also produced the following ESBLs: CTX-M-15, OXA-1, OXA-9, TEM-1. Among the 247 KPC-Kp strains we performed sequence typing on 41 isolates; all KPC-Kp tested belonged to the ST512 and carried the bla KPC-3 gene [22]; bla genes encoding OXA-9 and SHV-11 were also detected.…”
Section: Study Populationmentioning
confidence: 99%
“…Shields et al found that pneumonia was an independent risk factor for CZA clinical failure, while the receipt of renal replacement therapy (RRT) predicted microbiological failure and CZA resistance development [ 39 ]. Recently, clinical and microbiological failures with CZA have combined to the development of decreased susceptibility/resistance to this agent, as described in a case of septic thrombosis, a high clinical complexity condition [ 43 ], and in a case of delayed source control [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they revealed a strong impact of a high-inoculum effect on CFDC MICs, which is even more worrisome [ 65 ]. Tiseo et al described a case of recurrent KPC- Kp bacteremia successfully treated with MVB after in vivo, CZA-induced resistance development to CZA and CFDC [ 44 ]. Moreover, a case of a NDM producing E. col i intra-abdominal infection in a hematopoietic stem cell transplant recipient was reported where CFDC resistance evolved after 19 days of administration.…”
Section: Resultsmentioning
confidence: 99%
“…We observed the strongest trade-offs during cefiderocol resistance development of OXA-48 and KPC-2 against carbapenems and aztreonam (KPC-2). Such collateral sensitivity/functional trade-offs can open the path for alternative treatment strategies, and they have been successfully exploited in the clinical setting with a carbapenem-β-lactamase inhibitor combination against ceftazidime-avibactam and cefiderocol resistant K. pneumoniae harboring the natural KPC-31 [23]. However, the molecular causes of these collateral effects remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%